Online education for lifelong learning - Inoue, Yukiko (Information Science Publishing, 2007)
"This book provides theoretical understanding of the essential link between open and lifelong learning and online distance education. It also offers a critical discussion of distance, open and lifelong learning, with a focus on new and emerging challenges of online distance education in global learning communities" - Provided by publisher
Includes bibliographical references and index
Keywords: Enseignement à distance; Éducation ouverte; Éducation permanente - Enseignement assisté par ordinateur; Continuing education -- Computer-assisted instruction; Distance education; Open learning; E-Learning; Lebenslanges Lernen; Aufsatzsammlung